Studi distribusi temperatur pada tradisi bakar batu papua sebagai sistem pemanasan tradisional multi lapisan - Samuel Parlidungan Siregar (Prosiding SNTTM, 2025)
The Bakar Batu (Barapen) tradition is a communal cooking method practiced by the indigenous people of Papua, Indonesia, which utilizes heat from pre-heated volcanic stones arranged in layered systems with food, leaves, and soil. This study aims to analyze the vertical temperature distribution within this traditional multi-layered heating system and evaluate its thermal effectiveness in achieving complete food cooking. An experimental field approach was employed, involving the installation of K-type thermocouples at five vertical points from the stone base to the surface, accompanied by thermal imaging using an infrared camera. Temperature data were recorded over 90 minutes and analyzed using a one-dimensional transient heat conduction model, as well as temperature gradient and heat flux calculations. The results show a gradual upward propagation of heat, with the base stones reaching up to 510 °C and the food layer attaining a maximum temperature of 98 °C at minute 40. The highest heat flux was observed between the hot stone and food layer (2955 W/m²), indicating the most active zone of heat transfer. The core food temperature remained above 90 °C for over 20 minutes, which is sufficient for complete biological cooking. This research confirms that the Bakar Batu system demonstrates high thermal efficiency and can serve as a reference model for sustainable thermal system design rooted in local wisdom.